Novel approaches in food grade bigels properties and applications: A review - Karimidastjerd, Atefeh; Cetinkaya, Turgay; Tarahi, Mohammad; Singh, Lovepreet; Konar, Nevzat; Khiabani, Arezou Habibzadeh; Toker, Omer Said (ELSEVIER, 2024)
Food-grade bigels represent a highly innovative and versatile gel system within the food industry, characterized by their unique ability to combine the advantages of both oleogels and hydrogels. This dual-phase system can effectively address the limitations of each gel type and offers enhanced functionality. This review classifies foodgrade bigels and their properties, highlighting examples of novel methods in bigel preparation. Additionally, the study delves into the use of bigels as fat replacers, bioactive and probiotic capsulation systems, and active packaging materials, as well as their significant potential in emerging 3D/4D food printing and nanotechnologies. Choosing the optimal combination of hydrogels and oleogels along with appropriate preparation technology, helps achieve the desired techno-functional and sensory properties in bigel. Advances in 3D printing and nanotechnology have further enabled precise control over the bigel properties, facilitating customized formulations tailored to specific needs. Therefore, the food industry can significantly benefit from using bigels in various food sectors. The integration of sustainable ingredients such as plant-based and insect proteins in bigel production presents a promising avenue for reducing the ecological footprint of food production and disposal. Ongoing research and development in this area will be essential to optimize these systems for sustainability.
Keywords: Bigel; Biogel; Capsulation; Fat replacer; 3D printing; Hydrogel; Oleogel; DELIVERY; OIL; SCAFFOLDS; PHOSPHATE; SYSTEMS; HYBRID; STARCH; GELS; Biochemistry & Molecular Biology; Chemistry; Polymer Science